Attitudes toward COVID-19 Vaccination among Malaysian Residents in the First Half of 2021: An Internet-Based Study. - Al-Kadhim, Aws Hashim Ali; Malik, Normaliza Ab; Al-Ani, Sarah Taha Yousif; Aziz, Azrul Hafiz Abdul; Faizah Abdul Fatah; Syatirah Najmi Abdullah; Azlan Jaafar (Japan University of Health Sciences & Japan Inter, 2024)
Indexed by ERA